First Aid Medication and Remedies for Heart Failure: Pertolongan Pertama Obat dan Pengobatan untuk Gagal Jantung - Salomov Shoxabbos Nozimjon o’g’li (Universitas Muhammadiyah Sidoarjo, 2022)
Dear reader, this article provides information about the drugs used in heart failure, one of the diseases that are currently common ingangj . For most people, Heart Failure is a long-term condition that cannot be treated. But treatment can help keep symptoms under control, possibly for many years. The main treatment options are: healthy lifestyle changes , medications , devices installed on your chest to control heart rhythm, surgery . In most cases, a combination of treatment is required. Highlights: Heart failure is a common long-term condition that can be managed with treatment. Treatment options include medications, healthy lifestyle changes, devices for heart rhythm control, and surgery. A combination of treatments is often necessary to effectively manage heart failure. Keywords: Heart failure, Treatment options, Medications, Healthy lifestyle changes, Devices